Effects of growth hormone therapy on the onset and progression of pubertal development in girls with idiopathic short stature - Feng Zhu; Qi Xu; Lingxiao Huang; Jieqian Zhu; Lina Huang; Yu Zhang (Taylor & Francis Group, 2024)
AbstractObjective The aim of this study was to explore the impact of growth hormone (GH) therapy on the onset and progression of puberty in girls with idiopathic short stature.Methods This study included 541 girls aged between 4.5 and 10.6 years who were receiving GH treatment, monitored over a 22-year follow-up period. Of these, 126 girls have been followed up to the onset of menarche. The participants were divided into two groups: a ISS control group (n = 66) and a group receiving daily GH treatment at a dose of 0.15 iu/kg (n = 60). We assessed the pubertal development and GH usage of these girls every three months.Results (1) There was no significant difference in the onset of puberty between the growth hormone (GH) treatment group and the control group; however, the average duration of puberty was longer in the treatment group compared to the control group. (2) During puberty, there were no significant differences in height growth between the treated and untreated groups. (3) The duration of GH treatment showed a significant negative correlation with the age at onset of gonadal development and the age at menarche in females within the treatment group.Conclusion GH treatment does not seem to accelerate the onset of puberty but may extend its duration, without significantly impacting height growth during puberty. Additionally, longer GH treatment duration is linked to earlier gonadal development and menarche in females.